Cardiac arrhythmias secondary to hormone therapy in trans women. (4th May 2019) - Wamboldt, Rachel; Haseeb, Sohaib; Waddington, Ashley; Baranchuk, Adrian
ABSTRACT: Introduction : With greater social acceptance and the evolution of transgender medicine as a specialty, more trans women are seeking hormone therapy (HT). Several studies have identified an increase in cardiovascular disease in trans women, however no studies have investigated the incidence of arrhythmias. Using two cases from the authors' clinic as examples, we propose that hormone therapy in trans women may increase the risk of cardiac arrhythmias. Areas covered : A literature search of sex hormones and cardiac arrhythmias was conducted. Using sex hormone studies completed in cis individuals and animal models we identified several similarities to trans women on HT. In cis men, low levels of testosterone are associated with increased rates of atrial fibrillation and right ventricular outflow tract arrhythmias. The role of estradiol remains less clear but there is evidence to suggest that the administration of exogenous estrogen may increase the rates of cardiac arrhythmias in cis women. Expert opinion : Research in the field of transgender medicine is expanding. As more trans women initiate HT, we will have a larger database from which to collect information regarding the benefits and risks of treatment, including the potential side effect of arrhythmias.